2006
DOI: 10.1111/j.1744-313x.2006.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell‐derived factor 1 (SDF1) genetic polymorphism in a sample of healthy individuals, seronegative individuals exposed to human immunodeficiency virus type 1 (HIV‐1) and patients infected with HIV‐1 from the Brazilian population

Abstract: The interaction of viral and host factors is believed to determine not only the risk for initial human immunodeficiency virus type 1 (HIV-1) acquisition but also the course of the infection. Genetic polymorphisms in the chemokine receptors and their ligands were related to the susceptibility and resistance to HIV-1 infection. A polymorphism in the conserved 3' untranslated region of the stromal cell-derived factor-1 (SDF1) gene, which encodes a ligand of the CXCR4 receptor, has been related either to delayed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Health Care Current SDF1 3' A mutation potentially involved in protection against late stage of HIV1 stimulated disease [7]. The fact further can be supported from in vitro studies on peripheral blood mononuclear cells from ASYMPT and SYMPT patients where PBMCs from HIV1 carrier ASYMT patients express higher amount of SDF1.…”
Section: Issn: 2375-4273mentioning
confidence: 95%
See 1 more Smart Citation
“…Health Care Current SDF1 3' A mutation potentially involved in protection against late stage of HIV1 stimulated disease [7]. The fact further can be supported from in vitro studies on peripheral blood mononuclear cells from ASYMPT and SYMPT patients where PBMCs from HIV1 carrier ASYMT patients express higher amount of SDF1.…”
Section: Issn: 2375-4273mentioning
confidence: 95%
“…Since SDF1 is a minor allele, population with lower minor allele frequency of this allele have lower resistance against HIV1 progression after infection [6]. The SDF1 genotyping study conducted on Brazilian population covering 161 asymptomatic patients harbouring HIV1 infection (ASYMPT) versus 617 patients with AIDS status (SYMPT) shows that individuals harbouring homozygous allele for SDF1 (3' A) either does not progress to the stage of AIDS and does not die from AIDS if retroviral therapy is availed suggest that presence of SDF1 3' A mutation potentially involved in protection against late stage of HIV1 stimulated disease [7]. The fact further can be supported from in vitro studies on peripheral blood mononuclear cells from ASYMPT and SYMPT patients where PBMCs from HIV1 carrier ASYMT patients express higher amount of SDF1.…”
Section: Sdf1 and Hiv1mentioning
confidence: 99%
“…However, other studies did not find such a correlation (Ioannidis et al 2001, Watanabe et al 2003, Reiche et al 2006, while a third group of studies found a correlation with accelerated disease progression (Mummidi et al 1998, van Rij et al 1998, Daar et al 2005. SDF1-3'A distribution varies significantly between different populations, with frequencies from 2-9% in Africans and up to 54-71% in Oceania (Su et al 1999).…”
mentioning
confidence: 92%
“…The Brazilian population presents a complex genetic background, characterised by a high degree of miscegenation (Callegari-Jacques et al 2003, Pena 2005. In major Brazilian cities, CCR5-∆32 was found at frequencies of between 2-7% (Munerato et al 2003, Vargas et al 2006, Reiche et al 2008, Rigato et al 2008, CCR5-59029A between 39-44% (Rigato et al 2008), CCR2-64I at approximately 10% (Munerato et al 2003, Rigato et al 2008) and SDF1-3'A between 18-22% (Reiche et al 2006, Rigato et al 2008. Despite the moderate rates of HIV infection reported in Brazil, little is known about the influence of genetic polymorphisms on HIV disease progression in this population.…”
mentioning
confidence: 99%
“…4 Although Brazil has the largest number of HIV-infected people among the countries in Central and South America, 5 and an ethnically very diverse population, 6 there is a paucity of information regarding cohorts of serodiscordant couples. The few reports on this subject in Brazil have addressed genetic polymorphisms in CXCL12 7 and CCR5, 2 the presence of specific HLA alleles, 8 patterns of activation in CD4 + T and CD8 + T lymphocytes, 9 sexual transmission profiles, 10 or sociodemographic characteristics associated with HIV infection. 9 Reports evaluating cellular host proteins that interact with HIV during its replication cycle have not yet been published.…”
mentioning
confidence: 99%